Recent crustal motion in Vietnam and in the Southeast Asia region by continuous GPS data - Minh, Le Huy; Masson, Rédéric; Bourdillon, Alain; Fleury, Rolland; Hu, Jar-Ching; Hung, Vu Tuan; Thanh, Le Truong; Thang, Nguyen Chien; Thanh, Nguyen Ha (Vietnam Journal of Earth Sciences, 2015)
This paper presents an estimation of the velocity of the Earth’s crust in Vietnam and the Southeast Asian region,determined from the GPS data in nearly 8 years (4/2005-11/2013) at 5 sites in Vietnam (DBIV, PHUT, VINH, HUES andHOCM) plus more than 20 ones in Southeast Asia and other regions using GAMIT software. The horizontal velocityvectors in ITRF2005 at the considered Southeast Asia stations show that they drive to the south-eastward, but theKUNM, DBIV, PHUT, VINH and HUES (with velocity of about 31-36mm/yr) move faster than the HOCM, CUSV, NTUSand BAKO (with the velocity of 21.5-25.5 mm/yr); meanwhile the PIMO drives to the northwest with the velocity of 29.8mm/yr. The fact that the relative velocity vectors with respect to the Eurasian plate decrease from 9.4 mm/yr at VINH, 5.6mm/yr at HUES, 3.1 mm/yr at CUSV to 1.9 mm/yr at HOCM, as well as the increase of the motion azimuths from 104o atVINH, 138o at HUES, 204o at HOCM to 247o at CUSV shows that the Indochina block rotate clockwise; however, itsnorthern part moves faster than the southern one. The significant difference of the relative velocities with respect toSundaland at the stations, 1.4 mm/yr at BAKO, 2.9 mm/yr at VINH, 6.8 mm/yr at HUES, 9.3 mm/yr at HOCM, 10.7 mm/yrat NTUS and 11.7 mm/yr at CUSV) implicates that the Sundaland also undergoes a significant internal deformation. References Avouac J. P. & P. Tapponnier, 1993. Kinematic model of active deformation in Central-Asia, Geophys. Res. Lett., 20 (10), 895-898. Lê Duy Bách và Trần Văn Trị, 2000. Chương 3, Kiến tạo, Sách tra cứu các phân vị địa chất Việt Nam. Cục Địa chất và Khoáng sản Việt Nam. Calais E., M. Vergnolle, V. San’kov, A. Lukhnev, A. Miroshnitchenko, S. Amarjargal and J. Deverchere, 2003. GPS measurements of crustaldeformation in the Baikal-Mongolia erea (1992-2002); Implications for current kinematics of Asia,J. Geophys. Res., 108(B10), 2501,doi:10.1029/2002JB002373. Chamote-Rooke N. & X. L. Pichon, 1999. GPS determined eastward Sundaland motion withrespect to Eurasia confirmed by earthquake slipvectors at Sunda and Philippine trenches, EarthPlanet. Sci. Lett., 173, 439-455. Duong Chi Cong, 2006. GPS measurementsof horizontal deformation across of Lai Chau-DienBien (Dien Bien Phu) fault in Northwest ofVietnam, 2002-2004, Earth Planets Space, 58,523-528. Duong Chi Cong & K. L. Feigl, 1999. Geodetic measurement of horizontal strain acrossthe Red River fault near Thac Ba, Vietnam, 1963-1994, Journal of Geodesy, 73, 298-310. England P. & G. Houseman, 1986. Finitestrain calculations of continental deformation: 2.Comparison with the India-Asia collision zone,J. Geophys. Res., 91(B3), 3664-3676. England P. & P. Molnar, 1997. Activedeformation of Asia: from kinematics to dynamics,Science, 647-650, doi:10.1126/science.278.5338.647. Vy Quốc Hải, 2009. Xác định chuyển dịch tuyệt đối khu vực lưới GPS Tam Đảo - Ba Vì, Tạp chí Địa chất, A 311 (3-4), 22-30. Herring T. A., R. W. King, S. C. McClusky, 2009. GAMIT reference manual, Department ofEarth, Atmotspheric, and Planetary Sciences,Massachussetts Institute of Technology. Houseman G. & P. England, 1993. Crustalthickening versus lateral expulsion in the Indian-Asian continental collision, J. Geophys. Res,98(B7), 12233-12249. Hutchison C. S., 1989. Geologicalevolution of South-East Asia, Oxford, OxfordUniversity press. Metcalfe I., 2011. Tectonic framework andphanerozoic evolution of Sundaland, Gondwanaresearch, 19, 3-21. Michel G. W., M. Becker, D. Angermann,C. Reigber & Reinhart, 2000. Crustal motion in EandSE-Asia from GPS measurements, EarthPlanet Space, 52, 713-720. Michel G. W., Y. Q. Yu, S. Y. Zhu, C.Reigber, M. Becker, E. Reinhart, W. Simons, B.Ambrosuis, C. Vigny, N. Chamote-Rooke, X. L.Pichon, P. Morgan, S. Matheussen, 2001. Crustalmotion and block behaviour in SE-Asia from GPSmeasurement, Earth Planet. Science Lett., 187,239-244. Lê Huy Minh, Nguyễn Chiến Thắng, Trần Thị Lan, R. Fleury, P. Lassudrie-Duchesne, A. Bourdillon, C. Amory-Mazaudier, Trần Ngọc Nam, Hoàng Thái Lan, 2007. Ảnh hưởng của bão từ tới nồng độ điện tử tổng cộng vùng dị thường điện ly xích đạo Đông Nam Á quan sát được từ số liệu GPS, Tạp chí Các Khoa học về Trái Đất, T.29, (2), 104-112. Lê Huy Minh, K. Feigle, F. Masson,Dương Chí Công, A. Bourdillon, P. Lassudrie-Duchesne, Nguyễn Chiến Thắng, Nguyễn Hà Thành, Trần Ngọc Nam, Hoàng Thái Lan, 2010. Dịch chuyển vỏ Trái đất theo số liệu GPS liên tục tại Việt Nam và khu vực Đông Nam Á, Tạp chí Các khoa học về Trái Đất, T.32, (3), 249-260. Peltzer G. & F. Saucier, 1996. Present-daykinematics of Asia derived from geologic faultrates, J. Geophys. Res., 101, 27943-27956. Sone M. & I. Metcalfe, 2008: ParallelTethyan sutures in mainland Southeast Asia: newinsights for Palaeo-Tethys closure and implicationsfor the Indosinian orogeny, Comptes RendusGeoscience, 340, 166-179. Lê Tử Sơn, Vũ Văn Chinh và nnk, 2006. Động đất Đô Lương, Nghệ An M4,7 ngày 7/1 và M4,6 ngày 12/1 năm 2005. Tạp chí Các Khoa họcvề Trái Đất, 28(1), 51-60. Simons W. J. F., A. Socquet, C. Vigny, B.A. C. Ambrosius, S. H. Abu, C. Promthong, C.Subarya, D. A. Sarsito, S. Matheussen, P. Morgan,& W. Spakman, 2007: A decade of GPS inSoutheast Asia : Resolving Sundaland motion andboundaries, J. Geophys. Res., 112, B06420,doi:10.1029/2005JB003868. Simons W. J. F., B. A. C. Ambrosius, R.Noomen, D. Angermann, P. Wilson, M. Becker, E.Reinhart, A. Walpersdorf and C. Vigny, 1999. Observing plate motions in S. E. Asia: Geodeticresults of GEODYSEA project, Geophys. Res.Lett., 26(4), 2081-2084. Tapponnier P., G. Peltzer, A. Y. Le Dain,R. Armijo & P. Cobbold, 1982. Propagatingextrusion tectonics in Asia ; new insights fromsimple experiments with plasticine, Geology, 12,611-616. Tapponnier P., G. Peltzer, R. Armijo, 1986. On the mechanics of the collision betweenIndia and Asia, Geological Society, London,Special Publications, 19, 113-157. Tapponnier P., R. Lacassin, P. H. Leloup,U. Schärer, D. Zhong, H. Wu, X. Liu, S. Ji, L.Zhang & J. Zhong, 1990. The Ailao Shan/RedRiver metamorphic belt : Tertiary lest-lateral shearbetween Indochina and South China, Nature, 343,431-437. Trần Đình Tô, Nguyễn Trọng Yêm, K. Feigl, Dương Chí Công, Vy Quốc Hải, 2001: Vềhoạt động của đới đứt gãy Sông Hồng theo số liệu đo GPS, Tạp chí Các Khoa học về Trái Đất, T.23,(4), 436-441. Tran Dinh To, Nguyen Trong Yem, Duong Chi Cong, Vy Quoc Hai, W. Zuchievicz, Nguyen Quoc Cuong, Nguyen Viet Nghia, 2012. Recentcrustal movements of northern Vietnam from GPSdata, J. Geodynamics, Doi:10.1016/j.jog.2012.02.009. Nguyễn Văn Vượng, Tạ Trọng Thắng, Vũ Văn Tích, 2002. A new kinematic model for thecenozoic deformation along the Red River shearzone: implication for the Song Hong basinformation, J. Geology, Serie B, 19-20, 79-89. Nguyễn Đình Xuyên, 2004. Nghiên cứu dự báo động đất và dao động nền ở Việt Nam. Báo cáo tổng kết Đề tài độc lập cấp Nhà nước, Viện Vật lý Địa cầu, Viện KH & CN VN, Bộ KH & CN. Nguyễn Đình Xuyên, 2008. Nghiên cứu đánh giá độ nguy hiểm sóng thần vùng ven biển Việt Nam và các giải pháp phòng tránh, Báo cáo tổng kết đề tài cấp Viện Khoa học và Công nghệ Việt Nam, Viện Vật lý Địa cầu, Hà Nội. Wilson P. et al., 1998. Study provides dataon active plate tectonics in Southeast Asia region,Eos Trans. AGU, 79(45), 545-549.